Chronicle (Algebra and Discrete Mathematics, 2007)
The editorial board of the journal “Algebra and Discrete Mathematics” congratulates Yu. S. Samoylenko, Yu. A. Drozd, V. M. Bondarenko, V. V. Lyubashenko, V. L. Ostrovskiy, V. V. Sergeychuk and V. V. Kirichenko with awarding to them of the State Prize of Ukraine in the field of science and technology for the year 2007.